Needs Analysis of Development e-Module Assisted Virtual Lab on Dynamic Electrical Materials - Harlipadensi Harlipadensi; Azizahwati Azizahwati; M. Rahmad (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2023)
This research was conducted to develop learning media in the form of assisted e-modules virtual lab, thus a needs analysis is needed as the first step in developing e-modules. This type of research is descriptive qualitative research, and the instrument for collecting data from this research is in the form of student analysis questionnaire sheets. The research was conducted to determine the need for the development of learning materials in schools. The results of the analysis of the needs of 45 students obtained that 40% of students were generally passive in asking questions during the learning process, however, 62.2% of students actively expressed their opinions in learning, so 86.7% of students feel uninterested in learning if they only listen to the teacher's explanation, without involving their active participation. Furthermore, 88.9% of students feel happy if there are learning resources that can utilize Android or IT so that the learning materials are interactive. Then 88.9% of students need learning media that can be studied independently at home and 86.7% of students think that the difficult material is dynamic electricity. These results illustrate the need to develop assisted e-module learning media virtual lab on dynamic electricity.